Factors associated with gonarthrosis in patients older than 40 years treated at the Hospital Santa Rosa in 2018 - Báez Ayala, Ana Luz (2020)
Objective: To determine the factors associated with gonarthrosis in patients older than 40 years of the Hospital Santa Rosa in 2018. Materials and methods: An analytical, case-control (61 cases and 122 controls) study was carried out in patients older than 40 years of age with and without a diagnosis of gonarthrosis treated at the Hospital Santa Rosa in 2018. In both groups, associated factors such as age, sex, nutritional status, hypertension, type 2 diabetes mellitus, occupation, knee trauma, low back pain, metabolic syndrome and smoking were evaluated. Pearson's chi-squared test and OR (logistic regression) were used for the statistical analysis. Results: Eighty-eight point five percent (88.5 %) of the patients with gonarthrosis were females. Out of the patients with this disease, 68.9 % were housewives; the most frequent age range was 60 to 69 years in the case group (45.9 %) and 50 to 59 years in the control group (37.7 %). A significant association was found between the risk of suffering from gonarthrosis and having suffered low back pain (OR = 6.395; 95 % CI = 3.163 – 12.929) and being female (OR = 3.905; 95 % CI = 1.632 –9.342). Regarding the history of knee trauma and smoking, they did not show significance. Conclusions: It is concluded that females and low back pain are involved in the onset and progression of gonarthrosis. Age and occupation had a significant association with the occurrence of this disease.